STRUCTURE OF THE ASSOCIATIONS OF FISH IN THE CORAL REEF IN THE GUANAHACABIBES NATIONAL PARK, CUBA - Cobián-Rojas, Dorka; Claro-Madruga, Rodolfo; Chevalier-Monteagudo, Pedro Pablo; Perera-Valderrama, Susana; Caballero-Aragón, Hansel (Revista Ciencias Marinas y Costeras, 2011)
In order to execute the management plan for the Guanahacabibes National Park it is necessary to establish a guideline on the diversity and structure of the associations of fish, as well as their possible changes as a result of temporary and spatial variations. Visual censuses were conducted of all the species during the rainy and dry seasons of years 2007 and 2008 in the main reef areas. A total of 15 stations were evaluated by means of 6 transepts of 50 x 2 m. No significant differences were observed in the main indicators of the structure of the associations (diversity of species, density, biomass, sizes and trophic categories) between the rainy and dry seasons. Few species showed differences in their abundance as a result of their mobility and distribution. Fish density and biomass showed a positive correlation with the complexity of the substrate. The highest values were observed in the ridges on the reef slope, which show exceptionally high sills and complex relief. Although the trophic structure was dominated by carnivores, mainly the ictiobenthophagous (38% of total biomass), herbivores presented a high proportion (25%), which is an indicator of favourable conditions; however, the proportion of omnivores here was higher than in other regions. A total of 201 species were recorded in the entire area, an amount higher than in any other reef in Cuba. The subsistence fishing area established for the local community included predominantly small fish and little abundance of medium and big fish, which could be due to illegal fishing.